Meningkatkan Hasil Belajar Pada Siswa Kelas II SDIT Ar Risalah Secang Melalui Classroom Reading Program - Tibta Ilmiahwati, (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The study aims to determine the increase in learning outcomes from theimplementation of the classroom reading program. The approuch used in this aqualittative approach with the type of classroom actionresearch. Research location at SDITAr Risalah Secang with the subjectof class II student who do not amount to 20 siswa. Datacollection techniques used are tests and observations. Based on the result of the analysis,it can be concluded that the improvement of learning outcomes using the classroom readingprogram in thematic learning in grade II students og SDIT Ar Risalah Secang.The author wishes to try to increase interest in readingg and learning outcomesthrought action by implementing the classroom reading program.. The step of theclassroom reading peogram are,1) holding a class library by involving children in managingthe books in the library,2) using reading books as additional references in the learningprocess, 3) creating creative reading activities to produce what student have read.Clasically reading interest and learning outcomes increased from the initial conditions, thefirst activity, and the second activity, respectively by 30%,68%,and 75%. Clasically anincrease in reading interest and student learning outcomes is achieved.